PATIENT-REPORTED EXPERIENCES WITH VIRTUAL COVID-19 ASSESSMENT CENTRES IN HULU LANGAT, SELANGOR - Kannadasan, Kalaivane; Mohd Hairi, Farizah; Dahlui, Maznah; Azzeri, Amirah; Suli, Zailiza (Malaysian Journal of Public Health Medicine, 2024)
The COVID-19 pandemic necessitated the rapid implementation of telehealth services to manage the high volume of patients, presenting unique challenges and opportunities. This study investigates the acceptability, usability, and satisfaction of COVID-19 patients in the Hulu Langat district, Selangor, Malaysia, using SELANGKAH, a telehealth application utilized as a virtual COVID-19 Assessment Centre (CAC). Understanding patient experiences with telehealth is crucial for optimizing healthcare delivery and resource allocation during the pandemic. The purpose of this study is to evaluate the acceptance of the virtual CAC approach, delivered through the SELANGKAH app, in providing remote healthcare services and to identify factors influencing user experience.A cross-sectional study design was employed from March to July 2024, collecting data from 705 participants registered in the SELANGKAH application registry using a validated questionnaire developed from the same study. The questionnaire was distributed through the SELANGKAH application. Descriptive analysis was performed on sociodemographic characteristics, while inferential analyses, including Spearman correlation and multiple logistic regression, were conducted using SPSS Version 26.The analysis revealed that occupation and education level significantly influenced the usability and acceptability of telehealth services. Government employees and individuals with lower education levels reported lower scores, while unemployed/students and those with tertiary education showed higher acceptance and satisfaction. Significant predictors for higher acceptability included tertiary education (OR = 7.319, p = 0.001), being unemployed or a student (OR = 6.311, p = 0.001), self-employment (OR = 4.459, p = 0.002), and employment in the private sector (OR = 3.258, p = 0.008). Despite 71.2% of participants reporting high overall perceptions of usage, significant usability issues were identified, particularly in ease of use and necessary health facilities provision.These findings highlight the need for targeted improvements in telehealth systems, focusing on user experience, communication, and error handling. The study's implications underscore the importance of patient-centered design in telehealth applications, informing policymakers and stakeholders about optimizing telehealth services and resource allocation for better patient care outcomes.